Functionalization of textile materials by double barrier discharge plasma - Oliveira, Fernando R. (2012)
The pre-treatment of textile materials by non-thermal plasma technologies can offer many advantages over conventional chemical processes used to surface modification. This technology doesn’t involve the use of water and chemical reagents, resulting in a more eco-friendly and economical process. In this study air atmospheric pressure plasma treatment at normal ambient conditions was applied in various textile materials, namely: polyamide, polyester, acrylics and wool. The pre-treated textile materials were characterized using advanced instrumental techniques including X-ray photoelectronic spectroscopy (XPS), differential scanning calorimetry (DSC) atomic force microscopy (AFM) and scanning electron microscopy (SEM). Wettability analysis with different liquids was conducted to study static contact angle as well as surface energy and adhesion work of the plasma-treated fibrous materials. Chemical and physical characterization of the fabric confirmed significant surface alteration. Surface modification concerning the improvement of adhesion regarding a functionalizing substance, i.e. phase change materials (PCM) microcapsules was also investigated.